METHOD OF GALYORKIN FOR NONLINEAR SOBOLEV TYPE EQUATIONS - Lotfikar, R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
In this paper the following initial boundary value problem is considered: $$ \begin{cases}  L \left(\dfrac{\partial u(t, x)}{\partial t}\right)+Mu (t, x) = f (t, x), \\ u(0, x)=u_0(x), \\ D^{\gamma}u|_{\Gamma}=0, |\gamma|
Keywords: Galyorkin’s equations; Sobolev type equations; initial boundary value problem